Evaluation of homogeneity and genetic stability of REOLYSIN super( registered ) (pelareorep) by complete genome sequencing of reovirus after large scale production - Chakrabarty, Romit; Tran, Hue; tin, Yves; Yu, Zhenbao; Shen, Shi-Hsiang; Kolman, John; Onions, David; Voyer, Robert; Hagerman, Allison; Serl, Sarah; Kamen, Amine; Thompson, Brad; et al. (Applied microbiology and biotechnology, 2014)
REOLYSIN registered (pelareorep) is a proprietary isolate of the reovirus T3D (Type 3 Dearing) strain which is currently being tested in clinical trials as an anticancer therapeutic agent. Reovirus genomes are composed of ten segments of double-stranded ribonucleic acid (RNA) characterized by genome size: large (L1, L2, and L3), medium (M1, M2, and M3), and small (S1, S2, S3, and S4). The objective of this work was to evaluate the homogeneity and genetic stability of REOLYSIN registered . Sanger sequencing (SS) performed on test articles derived from the Master Virus Bank (MVB) and Working Virus Bank (WVB) identified many modifications when compared to GenBank reference sequences. Massively parallel sequencing (MPS) using Roche-454 sequencing was performed on REOLYSIN registered (100 L scale) and resulted in 69,821,115 bases and an average of 335 bases per read. Twenty-nine high confidence differences relative to the GenBank reference sequence were identified in REOLYSIN registered by MPS. Of those, 27 were previously identified by SS in the virus bank-derived test articles. Of the remaining two nucleotide differences, one was predicted to be silent at the amino acid level (L3 genome-T3163C, codon 1054, 86 % of the population was "T" and 13 % of the population were reported as "C"). The other modification was in the noncoding region (M1 genome-A2284A to A2284G), and A2284G was present in 97 % of the population. The results obtained from MPS were comparable to those from SS; both demonstrate a high level of homogeneity at the amino acid level and genetic stability of REOLYSIN registered . Finally, phylogenetic analysis of the REOLYSIN registered L1 genome segment showed close evolutionary relationship with its human homologs, serotypes Lang and Dearing.